Skill acquisition in sport research, theory and practice - Hodges, Nicola J. 1970-; Williams, A. M. (A. Mark) 1965- (Routledge, 2020)
Skill Acquisition in Sport gives academics, students, coaches and practitioners the broadest and most scientifically rigorous grounding in the principles and practice of the field. Fully revised, updated and restructured, the third edition integrates theory and practice, and provides more material on practical application than ever before. Divided into four sections- providing instruction and feedback, organizing effective practice, training high-level skills, and the theories and mechanisms underpinning skill acquisition- the book covers a full range of key topics, including: the role of errors and rewards in motor learning instructions, demonstrations andfeedback imagery in motor learning constraints-based andself-directed learning technique change, creativity training and visual gaze training practicing under pressure the neurophysiology of learning. Based on the latest research, including chapters on emerging topics, and written by a global cast of world-leading experts, Skill Acquisition in Sport is an essential textbook for any kinesiology or sport science student taking skill acquisition, expertise development or motor learning classes.